A case study on corporate social responsibility practices amongst selected private academic institutions in Malaysia - Zaleha, Ishak (2011)
Corporate Social Responsibility (CSR) has emerged as a form of sustainability governance with advantages to the economic, environment and social progress. CSR is believed to have a significant influence on corporate sustainability. With the increasing awareness and global demand for better CSR practices, companies should recognize and adopt them into their management practices. The element of CSR becomes very important since it could cover all aspects of management. lt depends on how the organisation wants to integrate it to the business plan. The corporate responsibility should begin from internal practices or in the organisation before translated it to external parties such as social and environmental concern. Many companies are implementing the CSR including the academic institutions. Universities can make the expectations of students and stakeholders by adopting a well-conceived CSR strategy in the same manner as other business practices. The elements of marketplace, workplace, community and environment should be prioritized for the basis of the strategic planning of the business. The same principles of strategic management should be applied to incorporating the CSR as part of the competitive advantage . ln this study, the Sunway University, Masterskills University College of Health Sciences, Open University Malaysia and Asia e University have been selected as samples to study. They have actively involved in social contribution activities as a part of their CSR initiatives. How they define the CSR and how